POST CERVICAL UTERINE TORSION IN A BUFFALO FOLLOWED BY PROTRUSION OF LARGE INTESTINE THROUGH VAGINAL TEAR AND TOTAL UTERINE PROLAPSE - Reddy, Y V PRIDHVIDHAR; GUNARANJAN, K SAI; JYOTHI, K (The Indian Journal of Animal Reproduction, 2020)
A pluriparous full term buffalo with a history of colic, constant changing of position from sternal recumbency tostanding and frequent straining with reduced feed intake for past two days was presented to the clinic. Upon vaginaland rectal examinations it was diagnosed as dystocia with post cervical right side uterine torsion of greater than180 . The animal was subjected to modified Schaffers method and a live calf was removed on application of traction.Immediately after calf removal, prolapse of uterus from tear in caudal vagina occured. Suture of the vagina was doneand prolapsed mass was replaced following normal procedure.
Keywords: Buffalo; Post cervical Uterine torsion; Protrusion; Intestines; Vaginal tear